HAK-HAK PEREMPUAN PASCA PERCERAIAN DALAM PERUNDANG-UNDANGAN NEGARA MUSLIM (INDONESIA, MALAYSIA, MESIR, DAN TURKI) - Nerisma Eka putri (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2024)
ABSTRACT Divorce is a problem in the marriage relationship that is considered as the final way. Problems regarding divorce are enshrined in conventional fiqh regulations to laws in the Muslim world. Based on the normative study of Islamic law, one of the implications of divorce is the guarantee of the rights that must be fulfilled by the husband after divorce for the former wife and children in the marriage bond. These rights are nafkah iddah, nafkah mut'ah, nafkah nadliyah to hadhanah. For this reason, researchers are interested in studying the topic of women's rights after divorce based on the perspective of conventional fiqh and the laws on marriage that occur in Muslim countries such as Indonesia, Malaysia, Egypt and Turkey, using three analytical glasses. This research uses library research and descriptive analytical approach to examine and analyze phenomena based on literature. So that the results can be found that based on vertical analysis glasses can be known about the comparison between family law and the legislation of each Muslim country. Based on horizontal studies, it can be found that there are similarities between Indonesia and Malaysia, while in Egypt the divorce process must be registered with the knowledge of the wife, and Turkey provides advice on wishes before taking the divorce route. Based on the diagonal study, the four countries are solid and strong in carrying out in accordance with the regulations that have been determined.